Synthesis and spectroscopic characterizations of hexakis[(1-(4?-oxyphenyl)-3-(substituted-phenyl)prop-2-en-1-one)]cyclotriphosphazenes: their in vitro cytotoxic activity, theoretical analysis and molecular docking studies - Dogan, Hacer; Bahar, Mehmet Refik; Caliskan, Eray; Tekin, Suat; Uslu, Harun; Akman, Feride; Gorgulu, Ahmet Orhan (Taylor & Francis Inc, 2022)
The hexachlorocyclotriphosphaze compound (N3P3Cl6, HCCP) was reacted with excess (E)-(1-(4 '-oxyphenyl)-3-(substituted-phenyl)prop-2-en-1-ones (2-11) to produce hexakis[(1-(4-oxyphenyl)-3-(substituted-phenyl)prop-2-en-1-one)]cyclotriphosphazenes (CP 2-11). The structures of products (CP 2-11) were confirmed using elemental analysis, FT-IR, MS spectral analysis as well as P-31, H-1 and C-13-APT NMR techniques and their thermal properties determined by TGA and DSC techniques. The HOMO-LUMO energy gap and chemical reactivity identifiers were calculated and HOMO and LUMO images were viewed. According to the calculations, all the chemical potential values of CP 2-11 are negative and it shown that the molecules are stable. The in vitro cytotoxic of CP 2-11 investigated and their activity potentials were evaluated by molecular docking studies with Autodock Vina softwares. CP 2-11 compounds were found to demonstrate cytotoxic activity against human cancer cell lines (A2780, LNCaP and PC-3). The CP 2-11 compounds reduced the cell viability against all cancer cell lines in the range 36%-90% especially. The results showed that these compounds are powerful candidate molecules for pharmaceutical applications.
Keywords: MTT assay; spiro-phosphazene; cytotoxicity; molecular docking; structural characterizations